Visible light driven photocatalytic degradation of fluoroquinolone levofloxacin drug using Ag2O/TiO2 quantum dots: A mechanistic study and degradation pathway - Kaur A.; Salunke D.B.; Umar A.; Mehta S.K.; Sinha A.S.K.; Kansal S.K. (My University, 2025)
Herein, we report the facile synthesis, characterization and photocatalytic degradation application of Ag2O/TiO2 quantum dots (QDs). The QDs were synthesized via a pH-mediated precipitation method and characterized in detail in terms of their morphological, compositional, structural, optical and photocatalytic properties. Detailed morphological studies confirmed the large scale formation of spherical Ag2O/TiO2 quantum dots with typical sizes of 2-9 nm. Surface analysis by XPS clearly revealed the presence of Ag+ and Ti4+ in the form of Ag2O and TiO2. Optical properties exhibited an absorption shift towards the visible light region i.e. 506 nm, a wide shift compared to TiO2 QDs (i.e. 394 nm) in the synthesized Ag2O/TiO2 QDs. As a photocatalyst, the synthesized material exhibited remarkable photocatalytic performance towards the degradation of levofloxacin drug under visible light as compared to bare TiO2. The higher photocatalytic activity was due to electron-hole pair separation which improved the light absorption (λ > 400 nm) and availability of active sites. Interestingly, the major intermediates of levofloxacin degradation were identified and a probable pathway was also proposed. The observed results clearly revealed that simply prepared Ag2O/TiO2 QDs could be an excellent candidate for the photocatalytic degradation of various harmful chemicals. © 2017 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.